A Familiar Limit?

Calculus Level 3

If A = lim n ( n n + 1 + ( n + 1 ) n n n + 1 ) n A=\lim_{n\to \infty}\left(\frac{n^{n+1}+(n+1)^{n}}{n^{n+1}}\right)^n

Answer 100 A \lfloor{100A}\rfloor .


The answer is 1515.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Apr 23, 2019

A = lim n ( n n + 1 + ( n + 1 ) n n n + 1 ) n A 1 case (see Reference) = exp ( lim n n ( n n + 1 + ( n + 1 ) n n n + 1 1 ) ) lim n f ( x ) h ( x ) = e lim n h ( x ) ( f ( x ) 1 ) = exp ( lim n n ( n + 1 ) n n n + 1 ) = exp ( lim n ( 1 + 1 n ) n ) = e e 15.1534 \begin{aligned} A & = \lim_{n \to \infty} \left(\frac {n^{n+1} + (n+1)^n}{n^{n+1}}\right)^n & \small \color{#3D99F6} \text{A }1^\infty \text{ case (see Reference)} \\ & = \exp \left( \lim_{n \to \infty} n\left(\frac {n^{n+1} + (n+1)^n}{n^{n+1}}-1 \right)\right) & \small \color{#3D99F6} \implies \lim_{n \to \infty} f(x)^{h(x)} = e^{\lim_{n \to \infty} h(x)(f(x)-1)} \\ & = \exp \left( \lim_{n \to \infty} \frac {n(n+1)^n}{n^{n+1}} \right) \\ & = \exp \left( \lim_{n \to \infty} \left(1+\frac 1n\right)^n \right) \\ & = e^e \approx 15.1534 \end{aligned}

Therefore, 100 A = 1515 \lfloor 100A \rfloor = \boxed{1515} .


Reference: 1 \color{#3D99F6} 1^\infty limit (2nd method)

Pedro Cardoso
Apr 23, 2019

A = lim n ( n n + 1 + ( n + 1 ) n n n + 1 ) n A=\lim_{n\to \infty}\left(\frac{n^{n+1}+(n+1)^{n}}{n^{n+1}}\right)^n A = lim n ( 1 + ( n + 1 ) n n n n ) n A=\lim_{n\to \infty}\left(1+\frac{(n+1)^{n}}{nn^{n}}\right)^n A = lim n ( 1 + ( n + 1 n ) n n ) n A=\lim_{n\to \infty}\left(1+\frac{\left(\frac{n+1}{n}\right)^{n}}{n}\right)^n A = lim n ( 1 + lim n ( 1 + 1 n ) n n ) n A=\lim_{n\to \infty}\left(1+\frac{ \lim_{n\to \infty} \left(1+\frac{1}{n}\right)^{n}}{n}\right)^n A = lim n ( 1 + e n ) n A=\lim_{n\to \infty}\left(1+\frac{e}{n}\right)^n Making p = n e p=\frac{n}{e} A = lim p ( 1 + 1 p ) p e A=\lim_{p\to \infty}\left(1+\frac{1}{p}\right)^{pe} A = ( lim p ( 1 + 1 p ) p ) e A=\left( \lim_{p\to \infty}\left(1+\frac{1}{p}\right)^p \right)^e A = e e A=e^e 100 A = 1515 \lfloor{100A}\rfloor=1515

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...